2020
DOI: 10.2174/1874434602014010312
|View full text |Cite
|
Sign up to set email alerts
|

Etiological Agents of Urinary Tract Infection and 7 Years Trend of Antibiotic Resistance of Bacterial Uropathogens in Sudan

Abstract: Introduction: Bacterial infections of the urinary tract represent a major cause of outpatient visits as well as hospital-acquired infections. As the prevalence of multidrug-resistant uropathogens is increasing, updated knowledge of the commonest bacterial causes and their susceptibility patterns is crucial for the proper selection and use of antimicrobial drugs and the development of effective local prescribing guidelines. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
1
4
1
Order By: Relevance
“…In general, the overall resistance rate surpasses 50% over the study period (Fig 1). Moreover, there were vancomycinresistant Enterococcus species (33.3%) in this study, which was a higher prevalence than a report (14.8%) by Melese et al in Ethiopia [36] but lower than 54% resistance reported in Sudan [29]. In addition, 6(50%) nitrofurantoin resistant Enterococcus species were isolated in this study which was higher than (9.8%) vancomycin and (0-40%) nitrofurantoin resistant Enterococcus species reported in England [37].…”
Section: Plos Onecontrasting
confidence: 66%
See 1 more Smart Citation
“…In general, the overall resistance rate surpasses 50% over the study period (Fig 1). Moreover, there were vancomycinresistant Enterococcus species (33.3%) in this study, which was a higher prevalence than a report (14.8%) by Melese et al in Ethiopia [36] but lower than 54% resistance reported in Sudan [29]. In addition, 6(50%) nitrofurantoin resistant Enterococcus species were isolated in this study which was higher than (9.8%) vancomycin and (0-40%) nitrofurantoin resistant Enterococcus species reported in England [37].…”
Section: Plos Onecontrasting
confidence: 66%
“…conducted in Bahir Dar, Ethiopia (30.5%) [26], India (38.84%) [27], India ((28.2%) [28], Sudan (91%) [29], but higher than the prevalence studies conducted in Iran (15%) [20] and India (15.9%) [30]. Geographic and population differences, study design, or the laboratory method used among studies may explain the difference in the prevalence rate.…”
Section: Plos Onementioning
confidence: 93%
“…The conducted researches revealed increase in frequency of detection of strains of uropathogenic bacteria resistant to currently used antibiotic preparations occurring in 2019-2019 compared with the data of 2017: 10.3% and 6.4% increases in resistances representatives of the Mycoplasmataceae family to ciprofloxacin and ofloxacin respectively, 4.8% and 4.0% in Enterobacteriaceae to chloramphenicol and ampicillin respectively, and 8.9% in Staphylococcus genus to vancomycin. The data we obtained correlate with the results of the studies carried out by Patwardhan et al (2017) and Saad et al (2020).…”
Section: Discussionsupporting
confidence: 86%
“…According to the data of Кarou et al (2012), bacteria of Escherichia coli, Klebsiella pneumoniae and K. ozenae, isolated from the clinical samples from patients suffering dysbiotic malfunctions of the reproductive system, were characterized by the highest level of resistance to ampicillinrespectively 60%, 72% and 50% of the strains, also 55%, 49% and 50% were resistant to amoxicillin/clavulanate, 63%, 50% and 30% to trimetaprim-sulfamethoxazole, 30%, 32% and 25% of the cultures to chloramphenicol. Saad et al (2020) revealed that in the conditions of quantitative and qualitative changes in the composition of microbiota of the urogenital tract of men and women of reproductive age, more than 60% of all isolates of enterobacteria were characterized by resistance to β-lactam antibiotics and preparations of the tetracycline group; 40-60% of the cultures were resistant to fluoroquinolones and around 30% of strains -to chloramphenicol. Over 70% of the isolates of Staphylococcus aureus were resistant to penicillins (including methicillin), co-trimoxazole, clindamycin and nalidixic acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation